BROMELAIN WASTE TEA COMPOST INDUCED BY LIGNINOLYTIC INOCULUM OF Trichoderma sp. ON THE GROWTH OF LEAF NUMBER AND CHLOROPHYLL CONTENT OF CHILI (Capsicum annuum L.) - Syafira Clarisa Huda; Bambang Irawan; Salman Farisi; Yulianty Yulianty (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2021)
Pineapple is one kind of fruit that contains a lot of nutrition.  The waste from residual pineapple processing is called bromelain.  Bromelain contains polymer complex in the form of organic sources from nature if it could be decomposed properly.  One way to exploited bromelain is by composting.  Composting is done with the help of fungi of Trichoderma sp. to speed up the decomposition process.  The resulting compost is aerated to increase the nutrients and form a further decomposition process in the soil.  The research was carried out from January till March 2021 in the Microbiology Laboratory Biology, Faculty of Mathematics and Science, University of Lampung.  The parameters of this research are the content of chlorophyll and the number of leaves.  This research used a completely Randomized Design with 7 treatments that are A1 (24 hours of mixed bromelain), A2 (48 hours of mixed bromelain), A3 (72 hours of mixed bromelain), A4 (24 hours of pure bromelain), A5 (48 hours of pure bromelain), A6 (72 hours of pure bromelain), and A7 (control).  Based on this research the value of the highest chlorophyll A on A6 treatment is 0,655.  A value of the highest on chlorophyll B on A6 treatment that 0,429.  The highest total chlorophyll on the A6 treatment is 1,048.  Based on this research the A4 treatment has the highest average number of leaves compared to other treatments.